Perspectives on the strategic partnership for the protection of human rights and the problem of using digital personal data - Stoyatska, Ganna (Technium Social Sciences Journal, 2020)
The current and probable consequences of digitalization standards implementation into various personal data collection programs are analyzed. China’s example demonstrates the risks concerning business ethics and practices adherence while the analysis and processing of personal data. It is emphasized that the issues of the human rights and freedoms observance and their possible violations are urgent in the context of the total use of algorithms for processing personal behavior and personal trajectory of existence data.